A cross‐sectional study of stool form (using Bristol stool chart) in an urban South Indian population. Issue 6 (25th April 2019) - Srinivas, Melpakkam; Srinivasan, Vijaya; Jain, Mayank; Rani Shanthi, Coimbatore Subramanian; Mohan, Viswanathan; Jayanthi, Viswanathan
Abstract : Background: There is paucity of data on Bristol stool form (BSF) in healthy South Indian residents. Aim: To determine the BSF types and associated factors in an urban bowel health noncomplainant population. Methods: This cross‐sectional study, performed using a self‐administered questionnaire among adult Chennai residents, compared BSF types by gender for various factors (age, occupation, bowel frequency, and defecation‐related abdominal pain). BSF types 1/2 and 6/7 were grouped as hard and loose stools, respectively. The statistical tests used were proportion test, χ 2, and Kruskal–Wallis tests ( P < 0.05 deemed significant). Results: The study cohort of 1402 subjects included 748 (53.3%) men and a third each of professionals, semiprofessionals, and "non‐office goers" (homemakers, retirees, students, and unemployed). A total of 97% had daily bowel movement, and 8.5% reported defecation associated abdominal pain. The BSF types in decreasing prevalence were: Type 3 (35.6%), Type 4 (32.5%), Types 1 or 2 (20.5%), Type 5 (6.9%), and Types 6 or 7 (4.5%). On gender comparison, significantly more men passed hard ( P = 0.03) or loose stools ( P = 0.001), while more women passed Type 3 ( P = 0.0002). Loose stools in men were associated with abdominal pain ( P = 0.0035). Women passing hard or loose stool types were slightly older (median age in 30s vs. 20s in Types 3–5) and had reduced stool frequency ( P = 0.026: hard; P = 0.006: loose). Conclusions: This South Indian noncomplainant cohort's most common stool types were BSF Types 3 and 4, with few gender variations in extreme stool types. Abstract : This first study of stool form in south Indian noncomplainants shows that the majority pass Bristol stool Types 3 and 4. There are few gender variations only in the extremes of stool types.